Craniomandibular osteopathy in a 7-month-old American Bully dog - Salinas C., Eben (2021)
An 8-month-old male American Bully dog was brought to the clinic for an abnormal structure in the ventral region on the left side of the jaw. On palpation, enlargement of the left mandibular ramus was identified, with pain when opening the mouth. In blood biochemistry, alkaline phosphatase and serum phosphorus increased considerably. X-rays identified a marked proliferation of the periosteum with soft tissue invasion in the mandible. Computed tomography ruled out temporomandibular disorders. Treatment with non-steroidal anti-inflammatory drugs was administered orally, allowing the patient to eat without discomfort two weeks after the start of treatment. The clinical, imaging and histopathology evidence was compatible with a case of craniomandibular osteopathy in a non-predisposed breed.